(untitled) (AYUSHDHARA, 2019)
Varicella Zoster Virus (VZV) is a worldwide pathogen known by many names: chickenpox virus, varicella virus, zoster virus and human herpesvirus 3 (HHV-3). VZV Infections are species specific to humans, but can survive in external environments for a few hours, maybe a day or two. Disease manifestations include chickenpox (varicella) and shingles (herpes zoster). The incidence and severity of herpes zoster affects upto 25% persons during their lifetime and increases with age due to an age - related decline in immunity against VZV. Populations at increased risk for Varicella zoster– related diseases include immunosuppressed persons and persons receiving biologic agents (tumor necrosis factor inhibitors). Skin complaints affects all ages from the Neonates to the elderly persons and cause harm in a number of ways such as- discomfort, disfigurement, disability etc. Besides this, they suffer from social stigma because skin lesions are visible and have a cosmetic importance. Visarpa is such skin condition which pays more attention towards pain and burning sensation apart from cosmetic value. Though the lesions of Visarpa / H.Z appears to be annoying, the pain and burning sensation is unbearable by the patient. Visarpa is one of the major skin diseases which is explained in detail apart from “Kushta” Vyadhi in all the Ayurvedic classics. This gives us an idea about the seriousness and significance of this disease. Based on Dosha predominance, they are seven types of Visarpa as per Charakaacharya. Visarpa occurs as an acute disease which may remain for 10-12 days and not a chronic one as Kushta (skin diseases).